Handbagged (NHB Modern Plays). - Buffini, Moira (Nick Hern Books, 2015)
For over a decade Margaret Thatcher met the Queen for a weekly audience. With all her previous Prime Ministers the Queen enjoyed a fairly informal relationship, but with Mrs Thatcher, things were different. Handbagged speculates on the relationship between these two very powerful and private women. This is the earlier, one-act version of Moira Buffini's later full length play of the same name. This play premiered as part of the Women, Power & Politics season at the Tricycle Theatre in 2010.